Cooperative participation of CagA and NFATc1 in the pathogenesis of antibiotics-responsive gastric MALT lymphoma - Hui-Jen Tsai; Kun-Huei Yeh; Chung-Wu Lin; Ming-Shiang Wu; Jyh-Ming Liou; Ping-Ning Hsu; Yi-Shin Zeng; Ming-Feng Wei; Chia-Tung Shun; Hsiu-Po Wang; Li-Tzong Chen; Ann-Lii Cheng; et al. (Cancer Cell International)
Abstract Background This study aimed to explore whether cytotoxin-associated gene A (CagA) can inhibit cell cycle progression by activating nuclear factor of activated T cells (NFAT) in lymphoma B cells and contribute to Helicobacter pylori eradication (HPE) responsiveness (complete remission [CR] after HPE) in gastric mucosa-associated lymphoid tissue (MALT) lymphoma. Materials and Methods We co-cultured three B-lymphoma cell lines (MA-1, OCI-Ly3, and OCI-Ly7) with HP strains (derived from HPE-responsive gastric MALT lymphoma) and evaluated the expression patterns of CagA, phosphorylated (p)-CagA (CagAP−Tyr), and CagA-signaling molecules, cell-cycle inhibitors, p-NFATc1 (Ser172), and NFATc1 using western blotting. Furthermore, we evaluated the association between nuclear NFATc1 expression in the tumor cells of 91 patients who received first-line HPE (59 patients with HPE responsiveness and 32 without HPE responsiveness) and HPE responsiveness and CagA expression in tumor cells. Results In HP strains co-cultured with B cell lymphoma cell lines, CagA was translocated to the nucleus through tyrosine phosphorylation (CagAP−Tyr) and simultaneously dephosphorylated NFATc1, subsequently causing nuclear NFATc1 translocation and stimulating the expression of p-SHP-2/p-ERK/Bcl-xL. Activated NFATc1 causes G1 cell cycle retardation in both MA-1 and OCI-Ly3 cells by triggering p21 and p27 production. Nuclear NFATc1 localization was significantly associated with the presence of CagA in gastric MALT lymphomas (80% [41/51] vs. 33% [13/40]; p < 0.001) and with HPE responsiveness (73% [43/59] vs. 25% [8/32]; p < 0.001). Patients exhibiting both the presence of CagA and nuclear NFATc1 localization responded more rapidly to HPE than those without (median interval to CR, 4.00 vs. 6.00 months, p = 0.003). Conclusions Our findings indicated that CagA and NFATc1 cooperatively participate in the lymphomagenesis of HPE-responsive gastric MALT lymphoma.